Creative responses to compromised beginnings in life: how to support families struggling with early difficulties. Issue 2 (2nd September 2017) - Rustin, Margaret
ABSTRACT: This paper discusses forms of intervention based on psychoanalytic understanding useful to families who are struggling with the impact of a young child with special difficulties of various kinds. It proposes that the crucial contribution of the clinician is to find meaning in the disturbing behaviour of the child and to convey this to both parents and child while being attentive to the high level of parental distress.